Experimental Study on Influence of Fitting Accuracy for Tapered Roller Bearing on Temperature Rise Characteristic - Shuai Mo; Jiabei Gong; Chao Yang; Xiaolin Cao (Jixie chuandong)
Tapered roller bearing is an important key component of the mechanical transmission system that supports the rotating shaft system. Its performance parameters and working state will have an important impact on the transmission characteristics of the equipment. The temperature rise effect in the bearing operation is the key factor to the bearing performance. In order to deeply study the influence mechanism of the fitting accuracy of the tapered roller bearing on the temperature rise characteristics， a bearing intelligent test bench is developed. The temperature rise of the bearing under different fitting accuracy conditions is studied by experimental means. The coupling law of the ring inside and outside fitting accuracy fitting accuracy and temperature rise of the tapered roller bearing are analyzed， the temperature rise characteristic curve of the tapered roller bearing with different fitting accuracy is obtained， and the theoretical support for the precise selection of tapered roller bearing parameters in high-end equipment is provided.